2004
DOI: 10.1016/j.trstmh.2003.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of intestinal parasitic infections in relation to nutritional status in Mexican schoolchildren

Abstract: Undernutrition and intestinal parasitic infections affect childhood development and morbidity in many developing countries. Undernutrition may increase susceptibility to parasitic infections which in turn impair the nutritional status of the host. The relationship between intestinal parasitic infections and nutritional status in 400 Mexican schoolchildren was investigated. More than half of the children in the study showed intestinal parasites and polyparasitism. The prevalence of helminth infections was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
4
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 13 publications
7
50
4
11
Order By: Relevance
“…However, a study done elsewhere has shown a higher prevalence of overall helminthic infections in stunted children compared to those in normally nourished children (10). In the present study, H. nana infection was found to be more common among stunted children than normally nourished children (p<0.05).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…However, a study done elsewhere has shown a higher prevalence of overall helminthic infections in stunted children compared to those in normally nourished children (10). In the present study, H. nana infection was found to be more common among stunted children than normally nourished children (p<0.05).…”
Section: Resultscontrasting
confidence: 57%
“…Studies from Brazil (9) and Mexico (10) have shown the influence of intestinal parasitic infections on the anthropometric indices of school age children. To the contrary, a study done in Ethiopia among under-five children has indicated that there is no significant association between malnutrition and intestinal parasitic infections (11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies relating AIDS patients to opportunistic infections have shown that HAART has contributed to HIV infection control and to the reconstitution of patient immune systems, leading to a reduction in the occurrence of opportunistic infections, including those caused by intestinal parasites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that prolonged use of HAART, particularly of protease inhibitors, has an important impact on user nutritional status. The relationship between infections caused by intestinal parasites and some nutritional indicators has been proven in numerous studies involving nutritional status, infection prevalence and intensity (14)(15)(16)(17)(18)(19)(20). Malnutrition has a serious influence on immunity aspects, including the production of cytokines and antibodies, particularly Th2 profile (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…En México, el mayor número de publicaciones sobre parasitosis intestinal se enfoca a los niños, tal vez porque el padecimiento tenga repercusión en su crecimiento y desarrollo. 1 De acuerdo con el XII Censo General de Población y Vivienda 2000 en México, se registraron 100 millones de habitantes; 6 millones (7.1%) hablan alguna de las 85 lenguas indígenas. En Jalisco se habla náhuatl, huichol, tarasco y zapoteco.…”
Section: Biodiversidad Parasitaria Entre Indígenas Y Mestizos Adultosunclassified